2021
DOI: 10.33549/physiolres.934772
|View full text |Cite
|
Sign up to set email alerts
|

A New Caco-2 Cell Model of in vitro Intestinal Barrier: Application for the Evaluation of Magnesium Salts Absorption

Abstract: Experimental data concerning the bioavailability of the different Mg-salts in human organism is inconsistent. Mg-absorption reported by clinical studies largely varies depending on the method used for evaluation. The aim of this study was to evaluate the bioavailability and accessibility of magnesium bound in different Mg-salt compounds, using an in vitro model of intestinal cell barrier. The study included a variety of inorganic (oxide, sulphate, chloride, carbonate) and organic salts (lactate, citrate, pidol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Mg 2+ supplements are available in various preparations, which all have a different bioavailability, sometimes resulting in side effects ( 277 ). There are a few animal and human studies that show a higher bioavailability of organic Mg 2+ salts (eg, magnesium citrate) compared with inorganic compounds (eg, magnesium oxide) ( 278-280 ), although most studies did not find any differences in bioavailability ( 281-284 ). Specifically for organic salts, Mg 2+ bioavailability has shown to be the most efficient for magnesium gluconate compared with other forms such as magnesium chloride ( 278 ).…”
Section: Potential Molecular Mechanisms Of Magnesium Involvement In C...mentioning
confidence: 99%
“…Mg 2+ supplements are available in various preparations, which all have a different bioavailability, sometimes resulting in side effects ( 277 ). There are a few animal and human studies that show a higher bioavailability of organic Mg 2+ salts (eg, magnesium citrate) compared with inorganic compounds (eg, magnesium oxide) ( 278-280 ), although most studies did not find any differences in bioavailability ( 281-284 ). Specifically for organic salts, Mg 2+ bioavailability has shown to be the most efficient for magnesium gluconate compared with other forms such as magnesium chloride ( 278 ).…”
Section: Potential Molecular Mechanisms Of Magnesium Involvement In C...mentioning
confidence: 99%
“…Kyselovič J. and others compared the bioavailability of a number of magnesium compounds: oxide, sulfate, chloride, carbonate, lactate, citrate, pidolate. The study revealed the best intestinal absorption of magnesium pidolate salt [9].…”
Section: Introductionmentioning
confidence: 91%